Parameter optimization for two-stroke direct-injection spark-ignition aviation kerosene engine - Wang, Ying; Zhou, Qiongyang (Thermal science and engineering progress, 2024)
•Effects of some parameters on combustion and performance of two-stroke RP-3 DI-SI engine were studied.•Ignition timing, compression ratio and scavenging/exhaust phase have obvious impacts, while scavenging port area shows little impact on engine performance.•Parameter optimization of combustion system was carried out based on genetic algorithm.•After optimization the two-stroke RP-3 DI-SI engine power increased by 7.6 % and thermal efficiency was enhanced by 3.2 %without knock. The type of two-stroke spark-ignition(SI) engine is still the main power sources of small and medium unmanned aerial vehicles. A transition from gasoline to aviation kerosene or light diesel fuel and from carburetor or port-injection equipment to direct-injection(DI) equipment is prevailing. However, the performance of two-stroke DI-SI engine fueled with aviation kerosene is not very good under medium and high loads. Therefore, using the two-stroke DI-SI kerosene engine modified from port-injection SI gasoline engine as the research subject, the effects of different parameters on engine combustion and performance were studied and parameter optimization was also carried out at high loads. Based on the optimal fuel injection parameters, the influences of ignition time, compression ratio, scavenging/exhaust port area and scavenging/exhaust phase on the operating characteristics of two-stroke engine were analyzed. It was indicated that ignition timing, compression ratio and scavenging/exhaust phase have obvious impacts on engine performance, while the scavenging port area shows little impact on engine performance. An optimization calculation with genetic algorithm was made by determining the optimal values of six parameters such as compression ratio, ignition time, scavenging port area, exhaust port area, scavenging phase and exhaust phase. After optimization, the power(P) of the engine was increased by 7.6 % and the thermal efficiency(η) was enhanced by 3.2 % without knock. The results will lay a foundation for further design and research of two-stroke aviation RP-3 SI-DI engine.